TFP convergence across European regions. - Adriana Di Liberto; Stefano Usai (European Regional Science Association (ERSA), 2010)
This paper proposes a fixed-effect panel methodology that enables us to simultaneously take into account both TFP convergence and the traditional neoclassical-type of convergence. We analyse a sample of 199 European regions between 1985 and 2006 and find the absence of an overall process of TFP convergence as we observe that TFP dispersion is virtually constant across two different subperiods. However, the absence of a strong process of TFP convergence hides interesting and complex dynamic patterns across regions as we observe significant changes in countries ranking. These results suggest that while obtaining fast growth in TFP is not simple, it appears to be a key factor in achieving fast GDP per capita growth. They also suggests a role for geography in the observed dynamics. Our results are robust to the use of different estimation procedures such as simple LSDV, Kiviet-corrected LSDV, and GMM √ la Arellano and Bond.
Keywords: O47; O33; C23; 330; TFP; technology diffusion; panel data